IPSJ Transactions on Computer Vision and Applications - Saito, Hideo
IPSJ Transactions on Computer Vision and Applications (CVA) is a peer-reviewed open access journal published under the brand SpringerOpen. The journal is dedicated to publishing high-quality research articles, reviews, and letters in all areas of fundamental and applied computer vision and its applications. In addition to traditional core subject areas in computer vision, the journal also covers a broad spectrum of pattern recognition research including, but not limited to, early vision, data structures and representations, machine learning, and matching and recognition. IPSJ Transactions on Computer Vision and Applications has been publishing Open Access articles from all over the world through a fair, rigorous, and rapid review process, guided by an international editorial board of eminent researchers.